Symposium 2: User Perspectives on the Pedagogical Differences Between Electronic and Paper Portfolios - Murray, Christopher; Pellow, Andrew; Hennessy, Scott; Currant, Neil; Higgison, Carol (Proceedings of the International Conference on Networked Learning, 2006)
This paper reports on a formative examination of the pedagogical impact of e-portfolios recently introduced to postgraduate medical education at the Bradford NHS Trust and undergraduate/postgraduate healthcare training at the University of Leeds. Early results suggest that there are differences emerging in the learners' perceptions of the development of reflective skills, ownership of work and the ability to present evidence for assessment depending on whether the students are using a paper or electronic portfolio. Preliminary findings also suggest that to be successful, e-portfolios need to have support from the users and their supervisors/mentors who provide feedback. The paper will also highlight issues for further discussion and future investigation such as the nature of ownership, assessing reflective ability and learning, time issues, and feedback.